Addressing vulnerabilities in communities facing infectious disease threats: A need for social science-driven assessments - Osborne, Jacob; Paget, John; Napier, David; Giles-Vernick, Tamara; Kutalek, Ruth; Rodyna, Roman; Ahmed, Syed Masud; Dückers, Michel (Journal of Global Health, 2022)
This article was published in the Journal of Global Health [© 2021 The Author(s) JoGH © 2021 ISGH] and the definite version is available at: http://dx.doi.org/10.7189/jogh.11.03003 The Journal's website is at: https://jogh.org/documents/2021/jogh-11-03003.pdf